Cervical Disc Replacement for Spondylotic Myeloradiculopathy - Sahoo, PK (Med J Armed Forces India, 2006)
BACKGROUND: Cervical disc replacement is a newer concept and rapidly developing surgical treatment. A prospective study was conducted to determine, if accurately implanted Bryan's cervical disc prostheses can provide relief from objective neurological symptoms and signs, stability and normal range of motion in cases of cervical disc prolapse with myeloradiculopathy. MATERIAL AND METHOD: Twenty patients underwent Bryan cervical disc replacement from Jan 2002 to Dec 2003. Young patients between age groups 21 to 50 years with degenerative cervical disc prolapse at C3-C7 with myeloradiculopathy were included in this study. Patients with significant facet joint arthropathy, unstable spine, trauma, tumour, osteoporosis and active infection were excluded from this study. Nurick's grading was used for quantifying the neurological deficit. Patients were operated by anterior cervical approach using a specially designed Bryan's cervical discectomy system. Neurological and radiological outcome was assessed post operatively and at 2,6,12 and 24 months follow up. Outcome analysis was carried out using modified Odom's criteria. The radiographic results were assessed by taking antero posterior (AP) and lateral radiographs of cervical spine to find range of motion and device position. RESULTS: The patients were in the age group of 31 to 50 years. There were 14 (70%) male and 6 (30%) female in this study. Neck pain and brachialgia were the presenting symptoms in all cases, 12 (60%) had radiculopathy and 8 (40%) had myelopathy. Single level disc prolapse was present as per Magnetic Resonance Imaging (MRI) in four (20%) at C4-C5, 12 (60%) at C5-C6 and 4 (20%) at C6-C7. Bryan's disc size 15 was used in 8 (40%) and size 17 was used in 12(60%) patients. During post-operative, 02, 06, 12, and 24 months follow up, the clinical outcome was excellent in 16 (80%) and good in 4 (20%) as per modified Odom's criteria. There was demonstrated improvement in flexion, extension and rotation clinically and radiologically during follow up. There was no migration or displacement of device. CONCLUSION: Cervical disc replacement for cervical disc prolapse with myeloradiculopathy represents an exciting new technology. Patients treated with the Bryan cervical disc prosthesis for single level cervical disc prolapse showed good to excellent improvement in neurological deficit. Clinically and radiologically maintenance of motion was found during follow up. More patients with longer follow up and post operative MRI to find out the protection to adjacent discs from abnormal stress will be required before this prosthesis is accepted as a treatment option.